1999
DOI: 10.1096/fasebj.13.13.1855
|View full text |Cite
|
Sign up to set email alerts
|

A role for β2integrins (CD11/CD18) in the regulation of cytokine gene expression of polymorphonuclear neutrophils during the inflammatory response

Abstract: Growing evidence supports the idea that adhesion via beta(2) integrins not only allows cellular targeting, but also induces intracellular signaling, which in turn activates functional responses of adherent cells. This study investigates whether beta(2) integrin-mediated adhesion of human polymorphonuclear neutrophils (PMN) has a functional impact on cytokine production. Aggregation of the beta(2) integrin Mac-1 (CD11b/CD18) by antibody cross-linking was found to induce substantial de novo synthesis of IL-8 mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 56 publications
(60 reference statements)
3
69
0
1
Order By: Relevance
“…The basis of the engagement of CD18-independent mechanisms is not clear. In an in vitro system in which CD18-indepenent pathways of transendothelial PMN migration were identified, IL-8 was shown to promote the CD18-independent emigration of PMN (8,24,26,39). In another study we showed that the E. coli induced the release of macrophage inflammatory protein-2 (our unpublished observation), the murine homologue of IL-8, in lung tissue, which could account for the observed CD18-independent tissue PMN sequestration and migration responses.…”
Section: Discussionmentioning
confidence: 69%
“…The basis of the engagement of CD18-independent mechanisms is not clear. In an in vitro system in which CD18-indepenent pathways of transendothelial PMN migration were identified, IL-8 was shown to promote the CD18-independent emigration of PMN (8,24,26,39). In another study we showed that the E. coli induced the release of macrophage inflammatory protein-2 (our unpublished observation), the murine homologue of IL-8, in lung tissue, which could account for the observed CD18-independent tissue PMN sequestration and migration responses.…”
Section: Discussionmentioning
confidence: 69%
“…Specifically, we found that primary macrophages and activated/differentiated monocytic cell lines exposed to fibrinogen up-regulate the expression of MIP-1␣, MIP-1␤, MIP-2, and MCP-1. Several prior reports had suggested that CD11b/CD18 contributes to fibrin(ogen)-stimulated NF-B activation and gene expression (20,21,29). To assess roles for the fibrinogen-binding CD18 integrins in macrophage chemokine secretion, we supplemented cultures with peptides and mAbs known to inhibit CD11b/ CD18-and CD11c/CD18-fibrinogen interactions (8 -12, 15, 20).…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies clearly established that cross-linking CD11b/CD18 or CD11c/CD18 can stimulate cellular activities (22, 29 -32), and some of those activities could also be stimulated by fibrinogen (22,29,30). However, the evidence that CD11b/CD18 mediates fibrinogen-stimulated signaling was less decisive.…”
Section: Discussionmentioning
confidence: 99%
“…Fib has also been shown to activate platelets through the ␣ IIb ␤ 3 receptor (27) and is thought to play an important role in activating platelet aggregation and clot retraction. Neutrophil interactions with surface-bound Fib via ␤ 2 integrins results in a substantial increase in the production of IL-8 and IL-1␤, a response that is abrogated in CD18-deficient mice (28). However, the synergistic effect of Fib plus fMLP on neutrophils described here is independent of the ␤ 2 integrins because neutrophils from three patients with leukocyte adhesion deficiency, whose cells lack these receptors, exhibit responses to Fib plus fMLP that are normal (Table III).…”
Section: Discussionmentioning
confidence: 99%